2019
DOI: 10.1155/2019/6283153
|View full text |Cite
|
Sign up to set email alerts
|

Low Bioelectrical Impedance Phase Angle Is a Significant Risk Factor for Frailty

Abstract: The phase angle, which is measured via bioelectrical impedance analysis (BIA), is a clinically important bioimpedance parameter used for nutritional assessment and evaluating the risk of various diseases, such as locomotive syndrome (LS). It remains unclear if the phase angle is associated with frailty (fragile state of physical and mental health). We therefore examined this association in a large prospective sample. Of 1081 individuals receiving health checkups, 550 (male; 235, female; 365) were enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 27 publications
5
32
1
2
Order By: Relevance
“…In addition, researchers obtained the trend of cyclical phase angle decrease with age for both sexes. 58 Lower PA values in women were also confirmed in other world reports, 59 , 60 in various ethnic groups. 61 …”
Section: Discussionsupporting
confidence: 84%
“…In addition, researchers obtained the trend of cyclical phase angle decrease with age for both sexes. 58 Lower PA values in women were also confirmed in other world reports, 59 , 60 in various ethnic groups. 61 …”
Section: Discussionsupporting
confidence: 84%
“…Generally, a low PhA may suggest deterioration of the cell membrane and cellular dysfunction. A low PhA is associated with frailty [15][16][17] as well as being associated with sarcopenia [18][19][20]. In this study, there was a significant association between the PhA and OH/ECW, but we excluded OH/ECW from the multivariate analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Our results indicate that the process of body weight loss is more physiologic in the experimental group that loses less FFM than the control group. Among the bioimpedance parameters measured with BIA, the phase angle (defined as the ratio of resistance (intracellular and extracellular resistance) to reactance (cell membrane-specific resistance) expressed as an angle) is a clinically important parameter used for nutritional assessment and for assessment of the risk of various disease [ 35 ]. Interestingly, as shown in Table 3 , herein, we found that patients who followed the LCD had a lower phase angle, at 4 months after EIGB placement, than patients who followed the LCKD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as shown in Table 3 , herein, we found that patients who followed the LCD had a lower phase angle, at 4 months after EIGB placement, than patients who followed the LCKD. In our opinion, this finding is clinically relevant considering that the phase angle represents both the amount and quality of soft tissue, with a high phase angle reflecting higher cellularity, better cell heath and better nutritional status [ 35 ].…”
Section: Discussionmentioning
confidence: 99%